Perancangan Lokapasar Terdistribusi Sebagai Publikasi Kalatog Produk UMKM - Haddad Sammir; Khairil Hamdi (Jurnal Manajemen Teknologi Informatika, 2025)
The use of information technology in sales is inevitable. There are many approaches that can be used such as developing an online store or joining a popular marketplace. Micro, Small and Medium Enterprises (MSMEs) can use the above methods, but still encounter obstacles such as lack of digital literacy and high resource and cost requirements. Developing a marketplace to support MSMEs also has its own challenges such as high technical requirements and costs. Therefore, this study offers a solution that takes a middle ground by building a distributed marketplace by sharing the technical burden of the marketplace with developers and MSME actors while still prioritizing efficiency and ease of operation.